2017
DOI: 10.1038/srep42563
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based repurposing of apigenin as a potential anti-fibrotic agent targeting hepatic stellate cells

Abstract: We have used a computational approach to identify anti-fibrotic therapies by querying a transcriptome. A transcriptome signature of activated hepatic stellate cells (HSCs), the primary collagen-secreting cell in liver, and queried against a transcriptomic database that quantifies changes in gene expression in response to 1,309 FDA-approved drugs and bioactives (CMap). The flavonoid apigenin was among 9 top-ranked compounds predicted to have anti-fibrotic activity; indeed, apigenin dose-dependently reduced coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…A study revealed that SMOC2 could modulate fibroblast proliferation and extracellular matrix deposition [43]. Similarly, a study revealed that expression of C1QTNF2 related to anti-fibrotic function [44]. Thus, SMOC2 and C1QTNF2 might play a similar function to protect from cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that SMOC2 could modulate fibroblast proliferation and extracellular matrix deposition [43]. Similarly, a study revealed that expression of C1QTNF2 related to anti-fibrotic function [44]. Thus, SMOC2 and C1QTNF2 might play a similar function to protect from cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several circulating molecules derived from other tissues can promote fibrotic responses in the liver through direct or indirect actions on hepatic stellate cells (see below). Informaticsbased approaches are increasingly utilized to uncover molecular signatures from tissue and stellate cells that can identify targets and predict outcomes (Hicks et al, 2017;Marcher et al, 2019;Ramnath et al, 2018;Wooden et al, 2017). From such studies, transcriptional (Marcher et al, 2019) and epigenetic (Moran- Sal-vador et al, 2019) drivers can be inferred and are remarkably conserved across different models of cellular activation, suggesting that stellate cell activation is a common pathway downstream of multiple fibrogenic signals in liver injury.…”
Section: Hepatocyte Injury and Deathmentioning
confidence: 99%
“…Upon chronic liver injury, quiescent HSCs undergo morphological and phenotypical transdifferentiation into contractile and highly proliferative myofibroblasts with collagen-producing ability. Plenty of polyphenols were found to protect liver from fibrosis via suppression of the activation of HSCs such as apigenin, EGCG, quercetin, icaritin, curcumin, and resveratrol [ 107 113 ]. The mechanisms underlying the inhibition of activated HSCs have been ascribed to upregulation of C1QTNF2, MMPs, or miR-221 to accelerate osteopontin degradation and downregulation of PPAR γ or membrane translocation and gene expression of GLUT2.…”
Section: The Potential and Mechanism Of Action Of Polyphenols In Tmentioning
confidence: 99%